Molecular Dynamics Simulations of Nanobubble Collapse Near Different Boundaries - Kadivar , Ebrahim; Rajabpour , Ali; Moctar , Ould el (Advances and Challenges in Science and Technology Vol. 3, 2023)
In this study, molecular dynamics simulations were used to investigate the dynamics of a single nanobubble caused by a shock wave collapsing close to two hard and one flexible boundaries. Molecular dynamics (MD) is a computer simulation method for analyzing the physical movements of atoms and molecules. The atoms and molecules are allowed to interact for a fixed period of time, giving a view of the dynamic "evolution" of the system. Polyethylene served as the flexible barrier, while aluminum and iron were used to create the stiff limits. A method called the momentum mirror was used to create the shock waves that hit the nanobubble inside a molecular system. The dynamics of a single nanobubble caused by shock and its collapse at flexible and stiff barriers were investigated in this work for two different distances from the walls. The boundaries' collapse-induced damage as well as the atomic velocity contours surrounding the single nanobubble were studied. The collapse-induced damage on the boundaries was obtained from ten collapsing nanobubbles. Results showed that the relative wall distance affected the single nanobubble's collapse dynamics near the boundaries. A generated nanojet was directed on the surfaces during the collapse process for all cases. In addition, the induced damages in the depth of the polyethylene surface, iron surface, and aluminum surface for the relative wall distance of \(γ\) = 1.3 were obtained as 6.0, 0.47, and 0.63 nm, respectively. It was observed that the depth of the collapse-induced damage for the nanobubble collapsing near the iron boundary was lower than the collapse-induced damage for the aluminum boundary. However, the erosion depth formed on the polyethylene boundary was much greater than the erosion depth of the two rigid boundaries. Furthermore, the damage width formed on the surfaces of polyethylene and aluminum was 12.0 nm and 7.0 nm, respectively. This shows that the erosion width for polyethylene was also much greater than the erosion width for aluminum. Finally, the damages formed on the boundaries for the relative wall distance of \(γ\) = 1.3 were more than the damages on the boundaries at relative wall distance of \(γ\) = 1.8.